2018
DOI: 10.4103/1673-5374.224378
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal stem cells versus adipose-derived mesenchymal stem cells for peripheral nerve regeneration

Abstract: Studies have confirmed that bone marrow-derived mesenchymal stem cells (MSCs) can be used for treatment of several nervous system diseases. However, isolation of bone marrow-derived MSCs (BMSCs) is an invasive and painful process and the yield is very low. Therefore, there is a need to search for other alterative stem cell sources. Adipose-derived MSCs (ADSCs) have phenotypic and gene expression profiles similar to those of BMSCs. The production of ADSCs is greater than that of BMSCs, and ADSCs proliferate fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Also, a loss of large myelinated fibers, together with an increase in smaller myelinated fibers is observed, which indicates that axonal sprouting is enhanced by the presence of ASCs. However, the axonal sprouting occures both intra-and extra-fascicular, and the myelin sheath is thinner than found for the sham group (Fernandes et al, 2018).…”
Section: Ad Ip Os E Tissue S Tem Cell S and Peripher Al Nerve Reg Ementioning
confidence: 52%
See 2 more Smart Citations
“…Also, a loss of large myelinated fibers, together with an increase in smaller myelinated fibers is observed, which indicates that axonal sprouting is enhanced by the presence of ASCs. However, the axonal sprouting occures both intra-and extra-fascicular, and the myelin sheath is thinner than found for the sham group (Fernandes et al, 2018).…”
Section: Ad Ip Os E Tissue S Tem Cell S and Peripher Al Nerve Reg Ementioning
confidence: 52%
“…Also, a loss of large myelinated fibers, together with an increase in smaller myelinated fibers is observed, which indicates that axonal sprouting is enhanced by the presence of ASCs. However, the axonal sprouting occures both intra‐ and extra‐fascicular, and the myelin sheath is thinner than found for the sham group (Fernandes et al., 2018). These findings can be interpreted that treatment with undifferentiated ASCs alone (with a vein as an outer guiding structure) does not promote peripheral nerve regeneration.…”
Section: Adipose Tissue Stem Cells and Peripheral Nerve Regenerationmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast to peripheral nerves, central nervous system injury is not followed by regeneration as it is limited by inhibitory mechanisms of glial regeneration and the non permissive microenvironment [10].…”
Section: Discussionmentioning
confidence: 99%
“… 32 Stem cells, such as neural stem cells and mesenchymal stem cells, have neuroprotective roles in peripheral nerve injury. 33 , 34 , 35 Attempts to enhance nerve regeneration and functional recovery with chemical compounds after SNI were also carried out in many studies. 36 , 37 In addition, studies have shown that artificial nerve conduits along with neurotrophins or stem cells can be used to regenerate peripheral nerves after injury as well.…”
Section: Discussionmentioning
confidence: 99%